DIVERSIFIKASI PENGOLAHAN HERBAL DALAM RANGKA MENGEMBANGKAN DIMENSI PRODUK TOGA DI DESA SIWALANPANJI - Moch. Dicky Riza; Endah Alamsari Andayani; Afifatus Karunia; Aulia Anaya Putri; Dwi Putri Eka Ratna Avifah; Izah Nurfitriyah; Novi Ardiani; Putri Nova Rizqi Febriyanti (STKIP PGRI Sidoarjo, 2022)
KKN is a learning activity in the field carried out by students as a form of community service. The thematic of KKN Mandiri at STKIP PGRI Sidoarjo is